How engineering instructors supported students during emergency remote instruction: A case comparison. Issue 3 (9th February 2022) - Douglas, Kerrie A.; Johnston, Amanda C.; Martin, Julie P.; Short, Taylor; Soto‐Pérez, Rene A.
Abstract: The rapid move to emergency remote teaching (ERT) during spring 2020 revealed many challenges for instructors, especially for the team and project‐based courses that previously relied on informal, in‐person interactions and laboratory equipment. The purpose of this case comparison study is to learn from this transition to identify ways that instructors can support the success of students in online, project‐based courses during times of crisis. We use data from student surveys, student and instructor interviews, and course documents to examine ways that student–student and student–instructor relationships changed during the move to ERT and how instructor decisions affected these relationships. We frame our work with social capital theory and social constructivism, specifically the community of inquiry framework. We examine two case studies: a first‐year engineering course and a junior‐/senior‐level engineering technology capstone course, both with large class sizes at a large research university. In both cases, students indicated that the shift to online learning decreased their access to relationships and supports from people who influenced their success and persistence. Although the instructors approached the transition differently, the data and analysis support recommendations for future moves to ERT in project‐based design courses. Recommendations include: Establishing mechanisms for informal conversations between students and between students and instructors; establishing a weekly routine that includes some level of real‐time, verbal communication; instructors being available for just‐in‐time feedback and questions as they arise; and establish a backup plan for ERT learning objectives, should the physical facilities no longer be accessible.